SINERGI WAKAF DAN KEUSAHAWANAN DI UNIVERSITY COLLEGE BESTARI: Waqf-Entrepreneurship Synergy at University College Bestari - Dwi Sari, Mutiara; Yusof, Ab. Aziz; Ibrahim, Anura (Jurnal Syariah, 2018)
The role of waqf in Higher Education Institutions is currently being discussed. Waqf has proven to be an effective instrument in higher education financing. However, waqf funds need to be optimized to ensure the sustainability of waqf itself. Therefore, all related parties should seek alternatives and solutions to ensure the sustainability of waqf. The first objective of this paper is to examine the management of waqf in higher education institution with a case study at University College Bestari (UCB), Terengganu, Malaysia. Secondly, to analyze issues of waqf sustainability and methods used UCB in ensuring the sustainability these waqf. This study is qualitative, data was obtained through library research and involving in-depth interviews of the two respondents. Data was analyzed using content analysis. The findings have found, the method used to sustain the waqf funds in UCB is by transparent management of assets through entrepreneurship activities for optimum benefit. The entrepreneurship activities are in the livestock, agriculture and business sectors. Another program is the development of entrepreneurship center within the campus. Besides, the formulation of a teaching and learning curriculum that included entrepreneurship elements was also conducted to ensure that students have basic entrepreneurial skills. This paper proves that waqf and entrepreneurship are inseparable. The synergies between waqf and entrepreneurship are important as an alternative to the sustainability of waqf itself.